Pengembangan LKPD Aljabar dalam Pembelajaran Matematika - Sutirah Sutirah; Leoni Tri Anisa; Syuta Ridho (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This study aims to develop teaching materials based on the TESMER approach on algebra material to improve the quality of mathematics learning at the junior high school level. TESMER as a development model is designed to bridge learning theory with classroom learning practices through systematic stages, namely the analysis, design, formative experiments, and retrospective reflection stages. The algebra material focused on includes algebraic forms, algebraic operations, and simple problem solving. This study uses a design research approach by involving teachers and students in the development process. The results of expert validation show that the teaching materials are included in the very valid category, with high assessments in the aspects of content integration, presentation, and language. Limited trials show that the teaching materials are practical to use by teachers and are liked by students. In addition, there was a significant increase in students' conceptual understanding and logical thinking skills after using the teaching materials. These findings recommend the TESMER approach as an effective framework in developing contextual algebra learning devices that are oriented towards meaningful learning.